Arbuscular mycorrhizal fungi (AMF) as a strategy to reduce the absorption of cadmium in cocoa (Theobroma cacao) plants - Pérez Moncada, Urley Adrian; Ramírez Gómez, María Margarita; Serralde Ordoñez, Diana Paola; Peñaranda Rolón, Andrea María; Wilches Ortiz, Wilmar Alexander; Ramírez, Luciano; Rengifo Estrada, Gersain Antonio (REVISTA TERRA LATINOAMERICANA, 2019)
Colombia is among the countries of Latin America that produce about 80% of f ine or “prime” cocoa of the world; however, cocoa in Colombia has limitations related to the presence of cadmium (Cd) in some soils where it is grown and this reduces the safety of the product. The objective of this study was to evaluate the absorption of cadmium in a cocoa pattern (IMC 67) in association with arbuscular mycorrhizal fungi (AMF) to determine their potential use as Cd immobilizers in medium and long-term. A randomized complete block design with three replications and 20 treatments was established, in 4 × 5 factorial arrangement, one control, three types of mycorrhizae (Glomus macrocarpum, Rhizoglomus intraradices and AMF-native) and f ive Cd doses (0, 6, 12, 18 and 24 mg kg-1). Plant height, dry weight of stem, leaves and roots as well as Cd concentration in stems, leaves and roots were measured. The results showed that cacao plants translocate the Cd easily, that is, they can live under these conditions since it was found in all organs (stems, leaves and roots); however, the treatment inoculated with AMF‑native decreased signif icantly the accumulation of Cd in all the organs evaluated. These results conf irm the benef icial effects that AMF have to alleviate the stress that plants shows when translocating heavy metals such as cadmium.